DEVELOPING CREATIVE THINKING IN ELEMENTARY STUDENTS THROUGH STEAM EDUCATION (Universal International Scientific Journal, 2026)
This article explores the mechanisms for enhancing creativity in elementary school students through one of the most effective trends in education today - the STEAM approach. The article is not just about theory, but about the art of turning a child's question "Why?" into an action question: "How can I create?"
Keywords: STEAM education, : Creativity, creative thinking, Abstract imagination, technology, teacher. learner, facilitator, innovation, education, creation.